Microwave-assisted pre-milling treatments of chickpea (Cicer Arietinum) for higher recovery - Solanki, Chandan; S. K., . Gupta; M. S. Alam, M. S. (Emirates Journal of Food and Agriculture, 2022)
This research was undertaken to examine the result of microwave pre-treatment on chickpea dehulling. The experiments were conducted at three microwave power levels (PL), 50, 70, and 90, at different five exposers from 1 to 3 minutes at the time interval of 30 seconds to evaluate chickpea dehulling with the pre-milling treatment of microwave exposure for achieving maximum dehulling yield, dhal yield, good dehulled grains in terms of quality with minimum dehulling loss. It was noted that dehulling yield improved with microwave power and exposure period. The highest dehulling yield, 71.02%, was achieved 90 PL with 2.5 minutes exposure and found maximum dhal yields, i.e., 66.40%, and minimum dehulling loss, 10.25%. So, this requirement was correct and better to get a higher dhal yield. These findings are also valuable for the pulse processing industry and fabricators for designing a continuous type pulse pre-milling treater unit. Hence, it could be highlighted that the microwave pre-milling treatment is more suitable for pulse processing like chickpea. This also presents an improvised method for pre-milling treatments for commercial adoption.